The world's first malaria vaccine - promising clinical results - Iga Dudek; Jakub Czarnota; Danuta Hajduga; Michał Dobrzyński; Magdalena Marzęda (Kazimierz Wielki University, 2019)
Work on the malaria vaccine has been going on since the early 20st century. The RTS,S/AS01 (Mosquirix) vaccine is the first and only in the world that has shown action against Plasmodium falciparum, a germ that contributes to the highest number of deaths from malaria. After passing the three phases of clinical tests positively, the fourth phase was launched in 2019 - the MVIP program (The Malaria Vaccine Implementation Program). It covers three African countries: Kenya, Ghana and Modawi. Around 360,000 children are expected to receive the vaccine from these countries annually. The third phase of Mosquirix vaccine testing lasted five years (2009-2014) and was based on the extraction of 15 459 children and infants from seven African countries, followed by the administration of four doses of each medicine. In four years, among children aged 5-17 months who received 4 doses of Mosquirix, 4 out of 10 (39%) managed to prevent the development of malaria. The number of hospitalizations for malaria and severe anemia, which is one of the consequences of this disease, has also decreased significantly. In the fourth phase of the study, the role of the vaccine in reducing the number of deaths in children and its safety will be assessed in the context of routine, global use. Data from the MVIP program will include WHO recommendations on the wider use of the vaccine.